Wykorzystanie standardu MDA (Model Driven Architecture) w modelowaniu baz danych - Sitarska, Monika (The use of MDA-solutions in data base modelling, 2005)
This article presents issues of a standard of complex programming solutions MDA (Model Driven Architecture), described by OMG (Object Management Group). The aim of this paper is also to characterize UML language in data base modelling.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 151-168